ANALISIS KANDUNGAN INFORMASI PROSPEKTUS INITIAL RETURN PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI IDX - Aris Sunandes; Artika Anissa Fatluloh (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
This study aims to analyze the Return on Assets (ROA) and Debt to Equity Ratio (DER) effects on Initial Public Offering (IPO) on financial companies listed on the Indonesia Stock Exchange. The research period was 2014-2106 with a sample of 36 financial companies which made an initial public offering on the Indonesia Stock Exchange. Companies that conduct Initial Public Offering show conditions as quite high classified. The results showed that Return on Assets (ROA) and Debt to Equity Ratio (DER) did not have a significant effect on initial returns on financial companies listed on the Indonesia Stock Exchange in 2014-2016